2008
DOI: 10.1016/j.infsof.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in Software Engineering: A systematic literature review

Abstract: __________________________________________________________________________________________This research presents a systematic literature review of motivation in Software Engineering. The objective is to report on what motivates and de-motivates developers, and how existing models address motivation. The majority of studies find Software Engineers form a distinguishable occupational group. Results indicate that Software Engineers are likely to be motivated according to: their 'characteristics' (e.g., their need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
298
2
31

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 389 publications
(368 citation statements)
references
References 80 publications
4
298
2
31
Order By: Relevance
“…Previous studies have shown that developer motivation and attrition are linked: highly motivated developers are more likely to remain in their current jobs, while lack of motivation may result in attrition [5,38]. This may be part of the reason that some GSD projects experience high staff turnover, and others do not: the nature of the work, and the working environment, in different kinds of GSD may reduce or exacerbate staff turnover.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that developer motivation and attrition are linked: highly motivated developers are more likely to remain in their current jobs, while lack of motivation may result in attrition [5,38]. This may be part of the reason that some GSD projects experience high staff turnover, and others do not: the nature of the work, and the working environment, in different kinds of GSD may reduce or exacerbate staff turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally software engineers were thought of as introverted, and this view was supported by many studies coming from Couger and colleagues' who measured Social Needs Strength of engineers [9] in their Job Diagnostics Survey. This view is not universal, as seen in the body of more recent research that identified software engineers as sociable people [5]. Certainly, the need for software engineers to communicate and relate to others is crucial in a GSD context [28]; this relatedness is one of the three dimensions of Ryan and Deci's "self determination theory" [34] (Fig.…”
Section: Software Engineer Turnover In Gsdmentioning
confidence: 99%
See 2 more Smart Citations
“…background, skills, values and motivational needs. Beecham et al [36] identifies several social factors effecting software engineer characteristics. For example, software practitioners prefer challenging tasks and therefore recognition in their work, stability in their organization, and most importantly they prefer to be socially identified with their team or group [36].…”
Section: Game Theoretic Perspectivementioning
confidence: 99%